Proceedings of the 13th International Conference on the Quality of Information and Communications Technology, QUATIC 2020 - Shepperd, Martin; Brito e Abreu, F.; da Silva, A. R.; Pérez-Castillo, Ricardo (2020)
This book constitutes the refereed proceedings of the 13th International Conference on the Quality of Information and Communications Technology (QUATIC'2020). The conference was held virtually due to the COVID-19 pandemic, in September 2020. The 27 full papers and 12 short papers were carefully reviewed and selected from 81 submissions. The papers are organized in topical sections: quality aspects in machine learning, AI and data analytics; evidence-based software quality engineering; human and artificial intelligences for software evolution; process modeling, improvement and assessment; software quality education and training; quality aspects in quantum computing; safety, security and privacy; ICT verification and validation; RE, MDD and agile.